ANALISIS AISAS MODEL TERHADAP “BTS EFFECT” SEBAGAI BRAND AMBASSADOR DAN INFLUENCER - LINA SINATRA WIJAYA; VIRGINIA - - (Universitas Bina Sarana Informatika, 2020)
BTS, is the most famous Korean idol group band boy currently not only in Indonesia but also around the world. It has become the target of many big companies to cooperate with them as the Brand Ambassadors or Influencers of their company products because of the huge benefits they can receive that eventually lead to the term